Digital Da'wah: The Role of Youtube in Enhancing Religious Literacy among Nahdlatul Ulama Youth - Naila, Tsania Mishbahun; Rohimi, Primi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
YouTube, as a media platform, has become an important means for preachers to spread da'wah studies, especially among teenagers from the Branch Children's Association (PAC), the Nahdlatul Ulama Student Association (IPNU), and the Nahdlatul Ulama Female Student Association (IPPNU) in Juwana District. This study investigates how da'wah content on YouTube can increase religious interest among teenagers, especially when they face difficulties in participating in da'wah directly. The novelty of this study lies in its innovative approach to utilizing digital media to convey religious messages, which are relevant to today's challenges. The methodology used is descriptive qualitative, with data collection through interviews and documents. Data analysis was carried out using the Miles and Huberman model technique. The findings demonstrate that da'wah content on YouTube is easily accessible and diverse, allowing teenagers to choose based on their interests. Furthermore, the discussions reveal that the da'wah videos significantly increase awareness and understanding of religion among the younger generation and positively impact their religious studies.